Performance of students with ADHD on global answer, short answer or multiple-choice questions - Ripoll Salceda, Juan C.; Lebrero Cristóbal, Sara; Yoldi Hualde, Mikel (Pulso. Revista de educación, 2016)
Recently several Spanish regiones have published guides which recommend accommodations in the assessment tests for students with ADHD. Some of the proposals are to use shortanswer or multiple choice questions. Given the lack of evidence supporting these proposals we collected data about performance of six students with ADHD who were evaluated with three types of questions on six texts. The results obtained with multiple choice questions were significantly higher than those obtained with short-answer questions, and these outperformed the essay questions.